Enumeration of Exotic Plants of Western Uttar Pradesh - Malik, Vijai; Mohammad, Inam; Pranita (Indian Forester, 2012)
The study records the occurrence and enumeration of 331 exotic species belonging to 265 genera and 83 families in Western Uttar Pradesh with emphasis on their habits and origins. Out of 331 exotic plants reported, herbs are represented by maximum number of 195 plants followed by trees 77, shrubs 33, vines 18, bamboos 4, palms 3 and parasite 1. Many of the exotic species in area have been introduced during the last few centuries for commercial, experimental and ornamental exploitations. American plants dominate in the Saharanpur forest division. Asteraceae are having the predominance of exotics in this region.